Implementasi Kelas Pemuridan “Saya Pengikut Kristus” Sebagai Model Pembinaan Iman Jemaat Di Gereja Sidang Jemaat Allah CFM Poris Tangerang - Faransina Ndolu (Vieka Wahana Semesta, 2026)
Abstract Discipleship Is The Essential Core Of The Church's Mission To Foster A Transformative Relationship Between Believers And Christ. However, Contemporary Discipleship Is Often Reduced To Mere Doctrinal Teaching Programs, Triggering A Gap Between Church Participation And Spiritual Maturity. This Phenomenon Also Occurs At Gsja Cfm Poris Tangerang, Where Congregants Actively Worship But Still Lack Personal Spiritual Disciplines. This Community Service (Pkm) Research Aims To Implement And Evaluate The